Features of individual and collective religious actions as characteristics of the degree of religious activity - Karassyova, Svetlana G.; Shkurova, Elena V. (Journal of the Belarusian State University. Sociology, 2019)
The article presents the results of studying the peculiarities in the cult (religious in nature and / or in form) behavior of the religious population in Belarus. The commission of individual and collective cult actions is one of the indicators of the multidimensional model of religiosity, used to study the multi-confessional environment. This indicator makes possible to determine the frequency, content and motivation for the implementation of religious practices. And it is the component of such characteristic of the population’ religiosity as the degree of religious activity. The research data allow to judge, that religious activity of Belarusians is connected to a large extent with the satisfaction of the need for social unity, based on a commonality of ideas and goals.
Keywords: religiosity; multidimensional model of religiosity; religion; cross-confessional approach; degree of religiosity; religious activity; religious practice